Artistic and health professionals perceptions of training load practices in pre-professional and professional ballet and/or contemporary dance - Fuller, M.; Moyle, G.; Harrison, C.; Minett, G. (Journal of Science and Medicine in Sport, 2021)
Introduction: It is useful to understand the perceptions of end-users to aid the uptake of injury reduction interventions. The perceptions of training load practices of artistic and health professionals` working in dance were investigated. Methods: Artistic staff (AS, n=6) and health professionals` (HP, n= 18) working in dance were invited to complete an online survey. Questions were developed from investigations in soccer (Weston, 2018; O`Brien & Finch 2016; 2017). The survey consisted of multiple-choice, Likert scale, and free-text responses. Results: Eighteen (n=24) respondents were from Australia (United Kingdom n=3, United States of America n=1, South America n=1, and Europe n=1). AS were perceived to be mostly/completely responsible for planning training (100% AS, 94% HP), with HP mostly/completely responsible at times of injury (83% AS, 83% HP). A performance season was reported to be very/extremely influential on planning training (100% AS, 89% HP). Discrepancies existed in reports of how frequently training was adjusted for individuals (83% often/a great deal AS, 33% HP), and for a group (83% AS, 28% HP). Reports of awareness of training monitoring were 50% agree/strongly agree for AS, and 83% for HP, with 50% of AS agree/strongly agree that monitoring occurs (17% HP). Both groups agree/strongly agree that training monitoring would be/is useful (83%). The highest perceived purpose of monitoring was to reduce injury by HP (78%). The highest number of responses for how frequent monitoring should occur were weekly for AS, and daily/weekly for HP. Fatigue, recovery and performance all received equal responses for what AS and HP wanted to know from monitoring. Discussion: This investigation provides insight into the perceptions of artistic staff and health professionals with experience in dance towards training load practices. Free-text responses in relation to the usefulness of training monitoring reveals that artistic staff respondents are not familiar with the practice, and display interest in learning more. Education of artistic staff may aid the implementation of training load monitoring. A recent investigation into health monitoring in professional ballet reported that dancers want their data to be shared with staff to provide insights into the association of scheduling and injury (Karreman et al., 2019). There is a lack of research on how to modify training loads to reduce injury, and suggestions have been made to apply training principles (Impellizeri et al., 2020). Further research should investigate the implementation of training load practices towards reducing injury in dance